VD_FINDINFO Décision / 2013 / 332 vom 23. Januar 2013 - VD Tribunal cantonal (2013)
CLASSEMENT DE LA PROCÉDURE, VIOLATION DE DOMICILE, MENACEDROIT PÉNAL | 177 al. 1 CP, 180 al. 1 CP, 181 CP, 186 CP, 319 CPP (CH)